2014
DOI: 10.5511/plantbiotechnology.14.0109c
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and characterization of chalcone isomerase-fold proteins from snapdragon (Antirrhinum majus L.) flowers

Abstract: cDNAs coding for the chalcone isomerase-fold proteins (CIFP) of the snapdragon (Antirrhinum majus L.) were cloned and characterized. One of these CIFPs was a Cluster-1 member of the CIFP family, which was a catalytically active chalcone isomerase and thus termed AmCHI1. The recombinant AmCHI1 could act on 2′,4,4′,6′-tetrahydroxychalcone (THC) and 2′,3,4,4′,6′-pentahydroxychalcone (PHC) to produce naringenin and eriodictyol with k cat /K m values of 0.25 s −1 µM −1 and 0.071 s, respectively, at pH 7.5 and 4°C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Thus, a split‐ubiquitin (SU) system (Iyer et al ., ) was used to screen for interactions between these P450 proteins and other soluble flavonoid enzymes in snapdragon [i.e. CHS (AmCHS1 or Nivea) (Hatayama et al ., ); CHI (AmCHI1) (Fujino et al ., ); F3H (AmF3H or Incolorata); DFR (AmDFR or Pallida); and C4′GT (AmC4′GT) (Ono et al ., ); Figures and S1]. Because the coding sequence of the snapdragon anthocyanidin synthase gene ( ANS ) was not available in databases, ANS was not included in these interaction assays.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, a split‐ubiquitin (SU) system (Iyer et al ., ) was used to screen for interactions between these P450 proteins and other soluble flavonoid enzymes in snapdragon [i.e. CHS (AmCHS1 or Nivea) (Hatayama et al ., ); CHI (AmCHI1) (Fujino et al ., ); F3H (AmF3H or Incolorata); DFR (AmDFR or Pallida); and C4′GT (AmC4′GT) (Ono et al ., ); Figures and S1]. Because the coding sequence of the snapdragon anthocyanidin synthase gene ( ANS ) was not available in databases, ANS was not included in these interaction assays.…”
Section: Resultsmentioning
confidence: 99%
“…Binary interactions among torenia flavonoid enzymes [i.e. CHS, two isozymes of type‐1 CHI (CHI1_1 and CHI1_2; Fujino et al ., ), FNSII (Akashi et al ., ; Ueyama et al ., ), F3H, DFR, ANS, F3′H (Ueyama et al ., ) and F3′5′H] were comprehensively analyzed using the SU and Y2H systems (Figures and S6). The analyses of yeast growth and β‐galactosidase activity in the SU system (Figure ) revealed FNSII interacted with CHI1_1, CHI1_2, F3H and DFR (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the authors suggested, it could be related to the role of flavonoids in nodule development, as signal molecules during interactions with rhizobia. Recently, it was concluded that CHILs are enhancers of flavonoid production and flower pigmentation, and their function is conserved among diverse land plant species (Fujino et al, 2014 ; Morita et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%